2021
DOI: 10.3126/jcmsn.v17i1.28543
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice on Prevention of Catheter-associated UTI among Nurses of a Tertiary Care Hospital

Abstract: Introduction: Urinary tract infection (UTI) is among the common bacterial infections worldwide and approximately 80% are associated with a urinary catheter. Catheter-associated UTI (CAUTI) has been associated with increased mortality, morbidity, length of hospital stay and the best way of CAUTI prevention is to adhere to recommended guidelines on infection control in the use of a urinary catheter. Methods: A cross-sectional analytical study was conducted among the nurses of college of medical sciences. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…These findings coincide with a study carried out by Marey et al ( 2020) who reported that statistical significant differences were found between nurses' knowledge and their gender. Also, these findings coincide with a study carried out by Mong et al (2022) who reported that the female nurses had achieved significantly higher knowledge levels Rashmi and Dhakal (2021), also had similar findings. This results weren't supported by Ayed (2015) who reported that no significant statistical differences were found between mean knowledge scores towards training course.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings coincide with a study carried out by Marey et al ( 2020) who reported that statistical significant differences were found between nurses' knowledge and their gender. Also, these findings coincide with a study carried out by Mong et al (2022) who reported that the female nurses had achieved significantly higher knowledge levels Rashmi and Dhakal (2021), also had similar findings. This results weren't supported by Ayed (2015) who reported that no significant statistical differences were found between mean knowledge scores towards training course.…”
Section: Discussionsupporting
confidence: 91%
“…Urinary tract infections (UTIs) are amongst the most prevalent bacterial infections in the world and 40% of HAIs, have serious cost and morbidity effects as well as a high death rate. Approximately 75% of UTIs acquired are associated with a urinary catheter at hospital (Rashmi & Dhakal, 2021).…”
Section: Introductionmentioning
confidence: 99%